Adsorption of Nitrate onto ZnCl2-Modified Coconut Granular Activated Carbon: Kinetics, Characteristics, and Adsorption Dynamics. (3rd June 2018) - Liu, Lingjie; Ji, Min; Wang, Fen
Abstract : Coconut granular activated carbon (CGAC) was modified by impregnating with ZnCl2 solution to remove nitrate from aqueous solutions. Sorption isotherm and kinetic studies were carried out in a series of batch experiments. Nitrate adsorption of both ZnCl2 -modified CGAC and CGAC fitted the Langmuir and Freundlich models. Batch adsorption isotherms indicated that the maximum adsorption capacities of ZnCl2 -modified CGAC and CGAC were calculated as 14.01 mgN·g −1 and 0.28 mgN·g −1, respectively. The kinetic data obtained from batch experiments were well described by pseudo-second-order model. The column study was used to analyze the dynamic adsorption process. The highest bed adsorption capacity of 1.76 mgN·g −1 was obtained by 50 mgN·L −1 inlet nitrate concentration, 20 g adsorbents, and 10 ml·min −1 flow rate. The dynamic adsorption data were fitted well to the Thomas and Yoon–Nelson models with coefficients of correlation R 2 > 0.834 at different conditions. Surface characteristics and pore structures of CGAC and ZnCl2 -modified CGAC were performed by SEM and EDAX and BET and indicated that ZnCl2 had adhered to the surface of GAC after modified. Zeta potential, Raman spectra, and FTIR suggested the electrostatic attraction between the nitrate ions and positive charge. The results revealed that the mechanism of adsorption nitrate mainly depended on electrostatic attraction almost without any chemical interactions.